(untitled) (Eurasian Research Bulletin, 2023)
Contraception is a method of preventing pregnancy during the premenopausal period, whereas hormone replacement therapy (HRT) is a medical treatment used to treat menopausal issues. The purpose of this study was to look at the effects of contraception and HRT on Vascular endothelial growth factor (VEGF) and Interleukin-6 (IL-6). One hundred (120) women were recruited: 30 with contraception, 30 with HRT, and 60 with no contraception, with HRT, and 60 with no as a control group. All women were between the ages of 31 and 70 and were categorized into four groups (31–40, 41–50, 51–60, and 61–70 In comparison to control women (without contraception and hormonal replacement therapy), the results of this study showed a significant increase in VEFG levels in all tested women (p <0.05).In comparison with the control group, there was a significant decrease (p 0.05) in IL-6 levels in women taking contraception and those taking hormonal replacement therapy. Based on these findings, it is possible to conclude that the administration of contraception and hormonal reproductive therapy affects the fibrinolytic system and increases the likelihood of thrombotic events>